Graphene Oxide Normal (GO + Mn2+) and Ultrapure: Short-Term Impact on Selected Antioxidant Stress Markers and Cytokines in NHDF and A549 Cell Lines - Stygar, Dominika; Pogorzelska, Aleksandra; Chełmecka, Elżbieta; Skrzep-Poloczek, Bronisława; Bażanów, Barbara; Gębarowski, Tomasz; Jochem, Jerzy; Henych, Jiří (Antioxidants (Basel, Switzerland), 2021)
Since biological applications and toxicity of graphene-based materials are structure dependent, studying their interactions with the biological systems is very timely and important. We studied short-term (1, 24, and 48 h) effects of ultrapure (GO) and Mn2+-contaminated (GOS) graphene oxide on normal human dermal fibroblasts (NHDF) and adenocarcinomic human alveolar basal epithelial cells (A549) using selected oxidative stress markers and cytokines: glutathione reductase (GR) and catalase (CAT) activity, total antioxidative capacity (TAC), and malondialdehyde (MDA) concentration, levels of vascular endothelial growing factor (VEGF), tumor necrosis factor-alpha (TNF-α), platelet-derived growth factor-BB (PDGF-BB), and eotaxin. GOS induced higher levels of oxidative stress, measured with CAT activity, TAC, and MDA concentration than GO in both cell lines when compared to control cells. GR activity decreased in time in NHDF cells but increased in A549 cells. The levels of cytokines were related to the exposure time and graphene oxide type in both analyzed cell lines and their levels comparably increased over time. We observed higher TNF-α levels in NHDF and higher levels of VEGF and eotaxin in the A549 cell line. Both types of cells showed similar susceptibility to GO and GOS. We concluded that the short-time exposure to GOS induced the stronger response of oxidative stress markers without collapsing the antioxidative systems of analysed cells. Increased levels of inflammatory cytokines after GO and GOS exposure were similar both in NHDF and A549 cells.
Keywords: A549; GO; graphene oxide; NHDF; cytokines; oxidative stress markers; graphene-based materials